Clostridioides Difficile Colonization Is Differentially Associated with Gut Microbiota Composition in Breastfed versus Formula Fed Infants (OR01-02-19). (13th June 2019) - Drall, Kelsea; Tun, Hein; Azad, Meghan B; Guttman, David; Sears, Malcolm; Mandhane, Puishkumar; Subbarao, Padmaja; Turvey, Stuart; Becker, Allan; Lefebvre, Diana; Morales-Lizcano, Nadia; Konya, Theodore; et al.
Abstract: Objectives: Colonization with Clostridioides difficile occurs in up to half of infants and is predicted by formula feeding. Although this microbe does not appear to pose any immediate risks for infants, its presence has been associated with susceptibility to chronic disease later in childhood, perhaps by promoting changes in the gut microbiome that may increase opportunity for colonization of pathogenic bacteria. We explored these compositional changes in exclusively breastfed, partially breastfed and exclusively formula fed infants to describe the microbial community and C. difficile colonization in infants with distinct diets. Methods: This study includes 1562 infants enrolled in the Canadian Healthy Infant Longitudinal Development (CHILD) Study. Infants provided a fecal sample at 3–4 months of age (Mean: 3.56, SD: 1.00) which was analyzed using 16S rRNA sequencing and targeted qPCR for C. difficile . Mode of feeding was recorded in a questionnaire at a 3 month follow-up visit. C. difficile colonization was defined as positive detection (CD+) in the fecal sample (reference: not present, CD-). Multivariate association with linear models (MaAslin) was used to determine changes in microbiota composition following arsine-square root transformation of relative abundances and FDR correction. Results: The prevalence of C. difficile colonization among all infants was 30.9%. Colonization rates differed among feeding groups: 22.63% of exclusively breastfed infants, 35.96% of partially breastfed infants and 49.63% of exclusively formula fed infants ( P  < 0.001). Microbes of the genus Bifidobacterium were decreased in CD + exclusively breastfed infants compared to non-carriers of the same diet (q = 0.02). Additionally, Blautia, Coprococcus and Clostridium, of the Lachnospiraceae family, and microbes of the Bacteroidetes phylum were of higher relative abundance (all q < 0.01) in breastfed CD + infants (both partial and exclusive). In exclusively formula fed infants, C. difficile colonization was not significantly associated with microbiota composition. Conclusions: C. difficile colonization may have a dysbiotic effect on the gut microbiota composition of breastfed infants, changes which have previously been associated with childhood atopy and obesity. Funding Sources: Canadian Institutes of Health Research (CIHR). AllerGen Network of Centres of Excellence (NCE)